HEPATITIS AND PHYSIOLOGY OF LIVER CELLS-A REVIEW - CHIGOZIE, UGWU GODWIN; Chikwendu, Ejere Vincent; Laurete, Okanya Chinagorom; Victor, Egbuji Jude (Innovare Journal of Ayurvedic Sciences, 2014)
Hepatitis means inflammation of the liver, with accompanying damage to liver cells. Hepatitis is classified into chronic and acute hepatitis and the different types are hepatitis A, B, C, D and E. However, their causes, modes of transmission, incubation periods, signs and symptoms, diagnosis, treatments and preventions were also discussed. Hepatitis causes liver diseases such as liver cirrhosis, hepatocellular carcinoma, and jaundice. It is reviewed that when chronic hepatitis C or B goes untreated, it causes scarring to the liver (cirrhosis) and an increased chance of liver cancer and liver failure, ending in death. Hepatitis viruses, especially Hepatitis A Virus (HAV), Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) infection are endemic in Nigeria and constitute a public health menace, the prevalence of HBV in some professional group was found to be highest among the female sex workers (FSWs). Global prevalence of chronic HAV and HBV infection is highest in Africa, Asia and Western Pacific; intermediate in Southern and Eastern Europe and Lowest in Western Europe, North America and Australia. Pregnant women, in the 3rd trimester of gestation are found to be more likely to be infected than those in the 1st and 2nd trimester, thus, the virus can be transmitted from the infected mother to the offspring during birth. The group of people who stood the high risk of contracting both HAV and HBV infections were also revealed. It is recommended that hepatitis screening should be incorporated in the routine antenatal check up, and government at all levels should be proactive in innovation and immediate implementation of a general child and adolescent immunization against HBV to prevent further spread of this virus. Key words: Hepatitis, Liver cell, cirrhosis, jaundice, hepatocellular carcinoma